2018
DOI: 10.3389/fphar.2018.00694
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidin Polymer-Rich Fraction of Stryphnodendron adstringens Promotes in Vitro and in Vivo Cancer Cell Death via Oxidative Stress

Abstract: Cervical cancer is the fourth most common cancer that affects women, mainly through human papilloma virus (HPV) infection with high-risk HPV16 and HPV18. The present study investigated the in vitro anticancer activity and mechanism of action of a proanthocyanidin polymer-rich fraction of Stryphnodendron adstringens (F2) in cervical cancer cell lines, including HeLa (HPV18-positive), SiHa (HPV16-positive), and C33A (HPV-negative) cells, and also evaluated in vivo anticancer activity. In vitro, cell viability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…All of the images were converted to grayscale images and then inverted and calibrated while using Image J. The mean fluorescence intensities were calculated as mean gray values that were derived from the sum of the gray values of all the pixels in the selection divided by the number of pixels [28,29,30].…”
Section: Methodsmentioning
confidence: 99%
“…All of the images were converted to grayscale images and then inverted and calibrated while using Image J. The mean fluorescence intensities were calculated as mean gray values that were derived from the sum of the gray values of all the pixels in the selection divided by the number of pixels [28,29,30].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a leaf fraction of Stryphnodendron adstringens containing gallic acid, procyanidin dimer B1, and (−)-epicatechin-3-O-gallate showed antioxidant activity and cytotoxicity toward human breast cancer cell lines [ 42 ]. A proanthocyanidin polymer-rich fraction from stem bark promoted in vitro and in vivo cancer cell death via oxidative stress in the cervical cancer model [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Filho, Ferreira, & Gouvêa, 2011) In other study, a model experimental to breast cancer and antitumoral potential concluded that the Barbatimão fractions decreased cancer cell viability as well as cell rounding-up, shrinkage, and nuclear condensation reduction of cell diameter and length and induced apoptosis (Sabino et al, 2017). A recent study demonstrated the in vitro and in vivo anticancer activity of a proanthocyanidin polymer-rich fraction of Stryphnodendron adstringens in cervical cancer cell lines HPV-positive (16 and 18), concluding that these cells treated with Barbatimão showed particular increase of free radicals and decrease of antioxidant species, mitochondrial membrane depolarization, progression to apoptosis as well as significant reduction of volume and induced weight tumoral (Kaplum et al, 2018).…”
Section: Anticancer Potential Of Stryphnodendron Adstringensmentioning
confidence: 96%